(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Purpose – Brand management is an essential concept in the current scenario of increased competition and customer expectation. The practise of brand management aids the marketing department in managing long term customer relation and loyalty. The main aim of the research paper is to analyze the role of brand management as an important tool of marketing to ensure customer loyalty and customer relation.Methodology – The use of books and journal as a source of secondary research support in providing relevant knowledge to the researcher about the research topic of marketing through branding. The use of relevant guide belonging to the year 2010-2013 maximizes the knowledge on the research topic. Results – The modern marketing techniques highly emphasizes on the concepts and techniques of brand management as an aid to marketing practices. The techniques of brand management support the growth of the customer base through awareness and influence of decision. Conclusion – The marketing manager focuses highly on the techniques of brand management so that improvement is assured in marketing management. The cost-effectiveness ensured by brand management is an additional benefit that supports managers in increasing investment in branding activities.